Kualitas Glulam Samama dengan Kombinasi Kayu Mangium dan Mahoni (The Quality of Samama Glulam and Its Combination with Mangium and Mahogany Wood) - Tekat D Cahyono; Fauzi Febrianto; Syarif Ohorella (Jurnal Ilmu dan Teknologi Kayu Tropis, 2017)
Previous study on several types of samama glulam had shown the MOE and MOR which is not meet JAS 2007. The recent study addressed the glulam construction from samama wood combined with two commercial woods to improve the quality of resulting glulam. Mangium (Acacia mangium) and mahogany (Swietenia mahogany) woods were laminated with samama wood using isocyanate adhesive at a spread rate of 200 g m-2 and then clamped with 30 cm gap between the clamp for 3 hours. Nine types of glulam were made with and without a combination of 1 cm lamina from the three types of wood species. The results showed the difference of density between samama glulam with the other types. Furthermore, the moisture content, hot water delamination, cold water delamination, MOE and MOR of the products have met the requirements of JAS 2007 for structural wood. Bonding strengths of most types of glulam have met the standard except for samama and mahogany glulam without the combination. The results of this study strengthened the potency of samama as glulam material for the structural application.Keywords: glulam, mahogany, mangium, samama, structural.